Pengaruh Influencer Rachel Vennya terhadap Minat Beli Pelanggan di Instagram - Atiqa Iffatin Faliha; Erlita Ridanasti (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to determine and analyze the effect of advertising disclosure on attractiveness in social media, determine and analyze the effect of advertising disclosure on trust in social media, determine and analyze the effect of advertising disclosure on skills in social media, determine and analyze the influence of the three components of source credibility on consumer buying interest on social media, and knowing and analyzing the influence of source expertise on consumer buying interest on social media. The samples taken are people who know Rachel Vennya on Instagram. The number of samples in this study is a minimum of 156 active Instagram users who know Rachel Vennya. The final data collected in this study were 251 respondents. Methods of testing and data analysis using Smart PLS. The results of this study indicate that there are significant results among all variables with the acquisition of a T-count > 3,000 to a P-Value of <0.05. These results show that Rachel Venya's advertisement disclosure by having attractiveness and expertise in promoting advertisements on her Instagram account has an influence on consumer trust, purchase intention, and interest.